Systematically-designed mixtures outperform single fibers for gut microbiota support - T.M. Cantu-Jungles; V. Agamennone; T.J. Van den Broek; F.H.J. Schuren; B. Hamaker (Gut Microbes)
Dietary fiber interventions to modulate the gut microbiota have largely relied on isolated fibers or specific fiber sources. We hypothesized that fibers systematically blended could promote more health-related bacterial groups. Initially, pooled in vitro fecal fermentations were used to design dietary fiber mixtures to support complementary microbial groups related to health. Then, microbial responses were compared for the designed mixtures versus their single fiber components in vitro using fecal samples from a separate cohort of 10 healthy adults. The designed fiber mixtures outperformed individual fibers in supporting bacterial taxa across donors resulting in superior alpha diversity and unexpected higher SCFA production. Moreover, unique shifts in community structure and specific taxa were observed for fiber mixtures that were not observed for single fibers, suggesting a synergistic effect when certain fibers are put together. Fiber mixture responses were remarkably more consistent than individual fibers across donors in promoting several taxa, especially butyrate producers from the Clostridium cluster XIVa. This is the first demonstration of synergistic fiber interactions for superior support of a diverse group of important beneficial microbes consistent across people, and unexpectedly high SCFA production. Overall, harnessing the synergistic potential of designed fiber mixtures represents a promising and more efficacious avenue for future prebiotic development.